2020
DOI: 10.3390/act10010007
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Shell Spherical Reflector Actuated with PVDF-TrFE Thin Film Strain Actuators

Abstract: This paper discusses the design and manufacturing of a thin polymer spherical adaptive reflector of diameter D=200 mm, controlled by an array of 25 independent electrodes arranged in a keystone configuration actuating a thin film of PVDF-TrFE in d31-mode. The 5 μm layer of electrostrictive material is spray-coated. The results of the present study confirm that the active material can be modelled by a unidirectional quadratic model and that excellent properties can be achieved if the material is properly anneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…This equation confirms that an electrostrictive material can be made piezoelectric by applying a bias electric field [18]. The method for determining the material properties (ε 1 , d 31 , Q 33 , P s ) has been described in [6,7]; they are reported in Table 1; the two values for P s refer to two independent methods of estimation. Notice that the value of the dielectric constant ε r has been found consistently smaller for the spray-coated samples than for the spin coated ones.…”
Section: Electrostrictive Pvdf-trfe Filmsupporting
confidence: 58%
See 4 more Smart Citations
“…This equation confirms that an electrostrictive material can be made piezoelectric by applying a bias electric field [18]. The method for determining the material properties (ε 1 , d 31 , Q 33 , P s ) has been described in [6,7]; they are reported in Table 1; the two values for P s refer to two independent methods of estimation. Notice that the value of the dielectric constant ε r has been found consistently smaller for the spray-coated samples than for the spin coated ones.…”
Section: Electrostrictive Pvdf-trfe Filmsupporting
confidence: 58%
“…Our work [6,7] investigates the control a thin spherical polymer shell covered with a thin film of electrostrictive copolymer (PVDF-TrFE) used as in-plane strain actuator (according to the d 31 mode); the target shape is obtained by applying voltages to a set of independent electrodes. Earlier work has shown that strain actuators are very efficient to control a flat plate; they are widely used in Adaptive Optics (AO) (e.g., see [8]).…”
Section: Large Reflectorsmentioning
confidence: 99%
See 3 more Smart Citations